2016
DOI: 10.5897/ajar12.1610
|View full text |Cite
|
Sign up to set email alerts
|

Yield performance of East African highland banana hybrids on farmers fields under high disease pressure

Abstract: The production of the East African highland cooking banana is constrained by pests, diseases and narrow genetic base amongst others. Research to develop resistant / tolerant genotypes has been on going at Kawanda. 18 promising banana hybrids have been identified. The hybrids were planted on farmers' fields in Kasangombe Sub-county in central Uganda for evaluation against black Sigatoka and yield. Data were collected on some of the agronomic traits, banana weevil damage and response to black Sigatoka disease on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…All banana cultivars grown in the Great Lakes region were susceptible to black Sigatoka (Tushemereirwe et al , , ; Johanson et al , ; Erima et al , ). Previously, the cultivar Yangambi KM5 was resistant, exhibiting a hypersensitive response to P. fijiensis infection (Carlier et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…All banana cultivars grown in the Great Lakes region were susceptible to black Sigatoka (Tushemereirwe et al , , ; Johanson et al , ; Erima et al , ). Previously, the cultivar Yangambi KM5 was resistant, exhibiting a hypersensitive response to P. fijiensis infection (Carlier et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The total number of functional leaves at flowering has been reported as a good indicator of a plant's tolerance/resistance to pests and diseases and correlates strongly with bunch weight (Alvarez, 1997). All plantain genotypes had at least eight functional leaves at flowering which improved good bunch development and high-quality fruits (Erima et al, 2016). Noupadja et al (2007) and Boyé et al (2010) also reported that to obtain heavier bunches and to increase yields, a sufficient number of functional leaves must be present on the plant from flowering to harvest.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, the index of non-spotted leaves (INSL) was higher on improved genotypes compared with Ebang. Erima et al (2016) also mentioned that the high rank of the youngest leaf with streaks, of the youngest leaf, spotted and the high number of functional leaves at flowering shows the tolerance of a genotype against Black Sigatoka. It also correlates significantly with disease development time (Craenen, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations